Edukasi Pengelolaan Sampah kepada Siswa SDIT Wisata Hasanah melalui Kuliah Lapangan ke TPA Batu Layang: indonesia - Kadaria, Ulli; Nugraheni, Putranty Widha; Aprillia, Ricka; Pramadita, Suci; Asbanu, Govira Christiadora (Jurnal Abdimas Madani dan Lestari (JAMALI), 2025)
The Integrated Islamic Elementary School (Sekolah Dasar Islam Terpadu, abbreviated as SDIT) Wisata Hasanah is one of the elementary schools in Pontianak City that implements the independent Murikulum Merdeka. In this curriculum, there is the Pancasila Student Profile Strengthening Project (Proyek Penguatan Profil Pelajar Pancasila, abbreviated as P5), where students actively address relevant issues in their surroundings. In a previous P5 activity, training on waste sorting based on its types—organic and inorganic—was conducted. A field lecture was held at the Final Disposal Site (TPA) of Batu Layang, Pontianak in this community service activity to raise awareness and concern for the environment, develop responsibility, independence, and critical thinking skills. Waste management education needs to be carried out from an early age to produce human resources with expertise in science and technology, in line with achieving Indonesia’s Golden Vision 2045. The students currently in elementary school will be the next generation to continue the nation's development. Activities at the TPA included delivering material, discussions, observations, and student feedback in the form of resumes and responses containing experiences, suggestions, input, and hopes. At the TPA site, students directly observed the facilities, infrastructure, and operational techniques of waste processing. The results of this activity included an increase in students' knowledge about waste management, an understanding of the impact of indiscriminate waste disposal and burning, and a commitment to environmental preservation. Community service is a form of collaboration and knowledge transfer between higher education institutions, elementary schools, and the government (Environmental Agency). Through this activity, it is hoped that students will develop environmental awareness and concern not only at school but also in their surrounding environment.